2012
DOI: 10.1111/j.1600-0668.2012.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in commercial aircraft high-efficiency particulate air (HEPA) filters assessed by PhyloChip analysis

Abstract: A biosensor that could be deployed in commercial aircraft would be required to function at an extremely low false alarm rate, making an understanding of microbial background important. This study reveals a diverse bacterial background present on aircraft, including bacteria closely related to pathogens of public health concern. Furthermore, this aircraft background is different from outdoor air, suggesting different probes may be needed to detect airborne contaminants to achieve minimal false alarm rates. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 41 publications
(76 reference statements)
3
42
0
1
Order By: Relevance
“…Proteobacteria was in general the most abundant phylum detected (55% of the sequences). Proteobacteria was also the dominant phylum observed in dust samples recovered from aircraft filters (Korves et al., ) and mall filters (Tringe et al., ). The next two most abundant phyla detected in the stores were Actinobacteria (19%) and Firmicutes (17%).…”
Section: Resultsmentioning
confidence: 95%
“…Proteobacteria was in general the most abundant phylum detected (55% of the sequences). Proteobacteria was also the dominant phylum observed in dust samples recovered from aircraft filters (Korves et al., ) and mall filters (Tringe et al., ). The next two most abundant phyla detected in the stores were Actinobacteria (19%) and Firmicutes (17%).…”
Section: Resultsmentioning
confidence: 95%
“…Indeed, BEs contain many potential novel habitats for microbial life that have chemical and physical properties not found in the natural world. Humans convey a large fraction of the colonizing microbes into these habitats by shedding them from their bodies or transporting them by means of their clothes and shoes, whereas the rest originate from water or other environmental sources (for example, soil) [4-7]. Depending on the environment, microbes can also be transported indoors by pets, insects and other animals [8].…”
Section: The Need For Culture-independent Analysis Of Microbial Divermentioning
confidence: 99%
“…Perhaps unsurprisingly, a great number of surface microbes can be traced back to human skin, although gut and nasal/oral environments also contribute [5,6]. Molecular studies of bacterial diversity in offices [5,12], hospitals [11], airplanes [7,38], kitchens [39] and restrooms [4] have consistently found a predominance of human skin-associated, and gastrointestinal or urogenital-associated, bacteria on most physical surfaces. In fact, Tringe and colleagues showed that the bacteria living on the skin of individuals inhabiting a particular space define the microbial community observed in air samples taken from that same space [13].…”
Section: Colonization and Dispersal Within The Built Environmentmentioning
confidence: 99%
“…However, more and more studies have investigated the microbial diversity of air in indoor environments since the first inventory of air was compiled by Radosevich et al. in ; (Angenent et al., ; Hospodsky et al., ; Kembel et al., ; Korves et al., ; Osman et al., ; Poza et al., ; Qian et al., ; Tringe et al., ). These tools allow to access of the huge microbial diversity, including non‐viable or not‐yet‐cultivable microorganisms which can induce allergic, toxic, and inflammatory responses (Gorny et al., ; Rinsoz et al., ) and must be taken into account.…”
Section: Introductionmentioning
confidence: 99%